Chromium alloy container and metal-supported electrochemical cell
Patent Information
- Application Number
- JP2024547554
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2023-10-05
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2043-10-05
AI Technical Summary
【0021】 本発明によれば、長期間に渡って合金部材どうしの接着性を維持可能なクロム合金容器及びメタルサポート形電気化学セルを提供することができる。
Smart Images

Figure 0007637832000004 
Figure 0007637832000005 
Figure 0007637832000006
Abstract
Description
[Technical field]
[0001] The present invention relates to a chromium alloy container and a metal-supported electrochemical cell. [Background technology]
[0002] Patent Document 1 discloses a chromium alloy container for housing a fuel cell. The chromium alloy container includes a first interconnector, a second interconnector, a separator, an anode frame, and a glass seal.
[0003] The first interconnector is connected to the air electrode of the fuel cell. The second interconnector is connected to the anode current collecting layer of the fuel cell. The separator is connected to the solid electrolyte of the fuel cell and separates the fuel gas and oxidant gas flow paths. The anode frame is disposed between the separator and the second interconnector. A glass seal bonds the first interconnector and the separator.
[0004] The first interconnector, the second interconnector, the separator and the fuel electrode frame are each made of a chromium alloy (for example, SUS430, SUS444, etc.) The glass seal is made of a glass material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent Publication No. 2015-156352 Summary of the Invention [Problem to be solved by the invention]
[0006] In the chromium alloy container described in Patent Document 1, the chromium contained in the first interconnector and the separator diffuses into the glass seal, which changes the composition of the glass seal and reduces its strength. As a result, the glass seal is deformed or cracked, making it impossible to maintain adhesion between the alloy members for a long period of time. This is a problem that is common to chromium alloy containers in general, not limited to containers that house fuel cells.
[0007] An object of the present invention is to provide a chromium alloy container and a metal-supported electrochemical cell capable of maintaining adhesion between alloy members for a long period of time. [Means for solving the problem]
[0008] The chromium alloy container according to the first aspect of the present invention has an internal space. The chromium alloy container includes a first alloy member made of an alloy containing chromium, a second alloy member made of an alloy containing chromium, and an adhesive portion that bonds the first alloy member and the second alloy member. The adhesive portion is composed of an oxide mainly composed of chromium and metal particles at least partially embedded in the oxide.
[0009] A chromium alloy container according to a second aspect of the present invention is related to the first aspect, wherein the metal particles contain, as a main component, the same element as a main component of at least one of the first alloy member and the second alloy member.
[0010] A chromium alloy container according to a third aspect of the present invention is the chromium alloy container according to the first or second aspect, wherein the metal particles contain chromium.
[0011] A chromium alloy container according to a fourth aspect of the present invention is related to any one of the first to third aspects, wherein in a cross section of the adhesive joint, the ratio of the area of the metal particles to the area of the oxide is 5% or more and 30% or less.
[0012] A chromium alloy container according to a fifth aspect of the present invention is related to any one of the first to fourth aspects, wherein an average distance between the metal particles in a cross section of the bonded portion is equal to or less than an average thickness of the bonded portion.
[0013] A chromium alloy container according to a sixth aspect of the present invention is related to any one of the first to fifth aspects, wherein the adhesive portion has an internal void.
[0014] A chromium alloy container according to a seventh aspect of the present invention is related to any one of the first to sixth aspects, wherein the chromium content in the metal elements in the oxide is 50 mol % or more.
[0015] A chromium alloy container according to an eighth aspect of the present invention is related to any one of the first to seventh aspects, wherein the oxide is composed of at least one of a chromium oxide and a chromium manganese oxide.
[0016] A chromium alloy container according to a ninth aspect of the present invention is related to any one of the first to eighth aspects, in which the oxide is crystalline.
[0017] A chromium alloy container according to a tenth aspect of the present invention is related to the ninth aspect, wherein the oxide has a spinel type or corundum type crystal structure.
[0018] A chromium alloy container according to an eleventh aspect of the present invention is related to any one of the first to tenth aspects, wherein the adhesive portion is a seal for sealing the internal space.
[0019] A chromium alloy container according to a twelfth aspect of the present invention is the chromium alloy container according to any one of the first to eleventh aspects, wherein the second alloy member has an embossed portion in contact with the first alloy member, and the adhesive portion adheres the embossed portion to the first alloy member.
[0020] A metal-supported electrochemical cell according to a thirteenth aspect of the present invention comprises a chromium alloy container according to any one of the first to twelfth aspects, and a cell body arranged on the chromium alloy container. The first alloy member has a plurality of communication holes that communicate with the internal space. The cell body is arranged on the first alloy member so as to cover the plurality of communication holes. Effect of the Invention
[0021] According to the present invention, it is possible to provide a chromium alloy container and a metal-supported electrochemical cell capable of maintaining the adhesion between alloy members for a long period of time. [Brief description of the drawings]
[0022] [Figure 1] FIG. 1 is a plan view of the electrolysis cell according to the first embodiment. [Diagram 2] FIG. 2 is a cross-sectional view taken along line AA of FIG. [Diagram 3] FIG. 3 is a partially enlarged view of FIG. [Figure 4] FIG. 4 is a cross-sectional view of an electrolysis cell according to a second embodiment. [Diagram 5] FIG. 5 is a partially enlarged view of FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] 1. First embodiment
[0024] (Electrolysis cell 1) Fig. 1 is a plan view of an electrolysis cell 1 according to a first embodiment, and Fig. 2 is a cross-sectional view taken along line AA in Fig. 1.
[0025] The electrolysis cell 1 is an example of a "metal-supported electrochemical cell" according to the present invention.
[0026] The electrolysis cell 1 is formed in a plate shape extending in the X-axis and Y-axis directions. In this embodiment, the electrolysis cell 1 is formed in a rectangular shape extending in the Y-axis direction when viewed in a plan view from the Z-axis direction perpendicular to the X-axis and Y-axis directions. However, the planar shape of the electrolysis cell 1 is not particularly limited, and may be a polygon other than a rectangle, an ellipse, a circle, or the like.
[0027] As shown in FIGS. 1 and 2, the electrolysis cell 1 includes a cell body 2 and a chromium alloy container 3 .
[0028] (Cell body 2) The cell body 2 is placed on a chromium alloy container 3. The cell body 2 is supported by a metal support 10 (described later) in the chromium alloy container 3. The cell body 2 has a hydrogen electrode 6 (cathode), an electrolyte 7, a reaction prevention layer 8, and an oxygen electrode 9 (anode).
[0029] The hydrogen electrode 6, electrolyte 7, reaction prevention layer 8, and oxygen electrode 9 are laminated in this order in the Z-axis direction from the chromium alloy container 3 side. The hydrogen electrode 6, electrolyte 7, and oxygen electrode 9 are essential components, while the reaction prevention layer 8 is optional.
[0030] [Hydrogen pole 6] The hydrogen electrode 6 is disposed on a first main surface 12 of the metal support 10 .
[0031] A source gas is supplied to the hydrogen electrode 6 through each supply hole 11 of the metal support 10. The source gas contains at least water vapor (H2O).
[0032] When the raw material gas contains only H2O, the hydrogen electrode 6 produces H2 from the raw material gas in accordance with the electrochemical reaction of water electrolysis shown in the following formula (1).
[0033] Hydrogen electrode 6: H2O+2e - →H2+O 2- (1)
[0034] When the raw gas contains CO in addition to H2O, the hydrogen electrode 6 converts the raw gas into H2, CO, and O2 in accordance with the electrochemical reactions of co-electrolysis shown in the following formulas (2), (3), and (4). 2- Generate.
[0035] Hydrogen electrode 6: CO2+H2O+4e - →CO+H2+2O 2- (2) Electrochemical reaction of H2O: H2O+2e - →H2+O 2- (3) Electrochemical reaction of CO2: CO2+2e - →CO+O 2- (4)
[0036] H2 generated in the hydrogen electrode 6 flows out from each supply hole 11 of the metal support 10 into an internal space 3a, which will be described later.
[0037] The hydrogen electrode 6 is a porous body having electronic conductivity. The hydrogen electrode 6 contains nickel (Ni). In the case of co-electrolysis, Ni functions as an electronic conductor and also functions as a thermal catalyst that promotes the thermal reaction between the generated H2 and the CO2 contained in the raw gas to maintain an appropriate gas composition for methanation, Fischer-Tropsch (FT) synthesis, etc. The Ni contained in the hydrogen electrode 6 is basically present in the form of metal Ni during operation of the electrolysis cell 1, but may also be partially present in the form of nickel oxide (NiO).
[0038] The hydrogen electrode 6 may contain an ion-conductive material, such as yttria-stabilized zirconia (YSZ), calcia-stabilized zirconia (CSZ), scandia-stabilized zirconia (ScSZ), gadolinium-doped ceria (GDC), samarium-doped ceria (SDC), (La,Sr)(Cr,Mn)O3, (La,Sr)TiO3, Sr2(Fe,Mo)2O6, (La,Sr)VO3, (La,Sr)FeO3, and a mixed material of two or more of these.
[0039] The thickness of the hydrogen electrode 6 is not particularly limited, but may be, for example, 1 μm or more and 100 μm or less. The thermal expansion coefficient of the hydrogen electrode 6 is not particularly limited, but may be, for example, 12×10 ―6 / ℃ or more 20×10 -6 / °C or less.
[0040] The method for forming the hydrogen electrode 6 is not particularly limited, and may be a firing method, a spray coating method (such as a thermal spray method, an aerosol deposition method, an aerosol gas deposition method, a powder jet deposition method, a particle jet deposition method, or a cold spray method), a PVD method (such as a sputtering method or a pulsed laser deposition method), or a CVD method.
[0041] [Electrolyte 7] The electrolyte 7 is formed on the hydrogen electrode 6. The electrolyte 7 is disposed between the hydrogen electrode 6 and the oxygen electrode 9. In this embodiment, the electrolyte 7 is sandwiched between the hydrogen electrode 6 and the reaction prevention layer 8 and connected to both of them.
[0042] The electrolyte 7 covers the hydrogen electrode 6 and also covers the area of the first main surface 12 of the metal support 10 that is exposed from the hydrogen electrode 6 .
[0043] The electrolyte 7 is a dense body having oxide ion conductivity. 2- is transferred to the oxygen electrode 9. The electrolyte 7 is made of an oxide ion conductive material. The electrolyte 7 can be made of, for example, YSZ, GDC, ScSZ, SDC, LSGM (lanthanum gallate), etc., with YSZ being particularly suitable.
[0044] The thickness of the electrolyte 7 is not particularly limited, but may be, for example, 1 μm or more and 100 μm or less. The thermal expansion coefficient of the electrolyte 7 is not particularly limited, but may be, for example, 10×10 ―6 / ℃ or more 12×10 ―6 / °C or less.
[0045] The method for forming the electrolyte 7 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0046] [Reaction prevention layer 8] The reaction prevention layer 8 is disposed between the electrolyte 7 and the oxygen electrode 9. The reaction prevention layer 8 is disposed on the opposite side of the electrolyte 7 to the hydrogen electrode 6. The reaction prevention layer 8 prevents a layer with high electrical resistance from being formed due to a reaction between a constituent element of the electrolyte 7 and a constituent element of the oxygen electrode 9.
[0047] The reaction prevention layer 8 is made of an oxide ion conductive material, and may be made of GDC, SDC, or the like.
[0048] The porosity of the reaction prevention layer 8 is not particularly limited, but may be, for example, 0.1% to 50%. The thickness of the reaction prevention layer 8 is not particularly limited, but may be, for example, 1 μm to 50 μm.
[0049] The method for forming the reaction prevention layer 8 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0050] [Oxygen pole 9] The oxygen electrode 9 is disposed on the opposite side of the hydrogen electrode 6 with respect to the electrolyte 7. In this embodiment, since the reaction prevention layer 8 is disposed between the electrolyte 7 and the oxygen electrode 9, the oxygen electrode 9 is connected to the reaction prevention layer 8. If the reaction prevention layer 8 is not disposed between the electrolyte 7 and the oxygen electrode 9, the oxygen electrode 9 is connected to the electrolyte 7.
[0051] The oxygen electrode 9 receives O transferred from the hydrogen electrode 6 through the electrolyte 7 according to the chemical reaction of the following formula (5): 2- produces O2 from
[0052] Oxygen electrode 9:2O 2- →O2+4e - (5)
[0053] The oxygen electrode 9 is a porous body having oxide ion conductivity and electron conductivity, and can be made of a composite material of one or more of (La,Sr)(Co,Fe)O3, (La,Sr)FeO3, La(Ni,Fe)O3, (La,Sr)CoO3, and (Sm,Sr)CoO3 and an oxide ion conductive material (such as GDC).
[0054] The porosity of the oxygen electrode 9 is not particularly limited, but may be, for example, 20% to 60%. The thickness of the oxygen electrode 9 is not particularly limited, but may be, for example, 1 μm to 100 μm.
[0055] The method for forming the oxygen electrode 9 is not particularly limited, and a baking method, a spray coating method, a PVD method, a CVD method, or the like can be used.
[0056] (Chrome alloy container 3) The chromium alloy container 3 has an internal space 3a through which the source gas supplied to the hydrogen electrode 6 and the reducing gas (H2 in this embodiment) generated in the hydrogen electrode 6 flow.
[0057] In this embodiment, the chromium alloy container 3 includes a metal support 10, a frame 20, an interconnector 30, a first seal portion 40, and a second seal portion 50. The internal space 3a is a space surrounded by the metal support 10, the frame 20, the interconnector 30, the first seal portion 40, and the second seal portion 50.
[0058] In this embodiment, one of the metal support 10 and the frame 20 is an example of the "first alloy member" according to the present invention, and the other is an example of the "second alloy member" according to the present invention. Also, in this embodiment, one of the frame 20 and the interconnector 30 is an example of the "first alloy member" according to the present invention, and the other is an example of the "second alloy member" according to the present invention.
[0059] [Metal support 10] The metal support 10 supports the cell body 2. In this embodiment, the metal support 10 is formed in a plate shape. The metal support 10 may be in the shape of a flat plate or a curved plate.
[0060] The metal support 10 is only required to be able to support the cell body 2, and its thickness is not particularly limited, but can be, for example, 0.1 mm or more and 2.0 mm or less.
[0061] As shown in FIG. 2, the metal support 10 has a plurality of supply holes 11, a first main surface 12 and a second main surface 13.
[0062] Each supply hole 11 penetrates the metal support 10 from the first main surface 12 to the second main surface 13. Each supply hole 11 opens to each of the first main surface 12 and the second main surface 13. Each supply hole 11 is covered by the cell body 2. Specifically, the opening of each supply hole 11 on the first main surface 12 side is covered by the hydrogen electrode 6. The opening of each supply hole 11 on the second main surface 13 side is connected to the internal space 3a.
[0063] Each supply hole 11 can be formed by mechanical processing (for example, punching), laser processing, chemical processing (for example, etching), or the like.
[0064] In this embodiment, each supply hole 11 is formed linearly along the Z-axis direction. However, each supply hole 11 may be inclined with respect to the Z-axis direction, and may not be linear. Furthermore, each supply hole 11 may be connected to another supply hole 11.
[0065] The first main surface 12 is provided on the opposite side to the second main surface 13. The cell body 2 is disposed on the first main surface 12. The frame 20 is joined to the second main surface 13 via a first seal portion 40.
[0066] The metal support 10 is made of an alloy containing Cr (chromium). Examples of such alloys include Fe-Cr alloy steel (stainless steel, etc.) and Ni-Cr alloy steel. The Cr content in the metal support 10 is not particularly limited, but may be 4% by mass or more and 30% by mass or less.
[0067] The metal support 10 may contain Ti (titanium) and / or Zr (zirconium). The Ti content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 1.0 mol% or less. The Zr content in the metal support 10 is not particularly limited, but may be 0.01 mol% or more and 0.4 mol% or less. The metal support 10 may contain Ti as TiO2 (titania) or Zr as ZrO2 (zirconia).
[0068] [Frame 20] The frame 20 is a spacer for forming the internal space 3a. In this embodiment, the frame 20 is formed in an annular shape.
[0069] The frame 20 is joined to the metal support 10 via the first seal portion 40 , and is joined to the interconnector 30 via the second seal portion 50 .
[0070] The thickness of the frame 20 is not particularly limited, but may be, for example, 0.1 mm or more and 2.0 mm or less.
[0071] The frame 20 is made of an alloy containing Cr. Examples of such alloys include Fe-Cr alloy steel and Ni-Cr alloy steel. The Cr content in the frame 20 is not particularly limited, but may be 4% by mass or more and 30% by mass or less. The composition of the frame 20 may be the same as or different from that of the metal support 10.
[0072] [Interconnector 30] The interconnector 30 is disposed on the opposite side of the metal support 10 with respect to the frame 20. The interconnector 30 is a member for electrically connecting the electrolytic cell 1 to an external power source or another electrolytic cell.
[0073] In this embodiment, the interconnector 30 is formed in a plate shape. The interconnector 30 may be in the shape of a flat plate or a curved plate.
[0074] The interconnector 30 is joined to the frame 20 via the second seal portion 50 .
[0075] The thickness of the interconnector 30 is not particularly limited, but can be, for example, not less than 0.1 mm and not more than 2.0 mm.
[0076] The interconnector 30 is made of an alloy containing Cr. Examples of such alloys include Fe-Cr alloy steel and Ni-Cr alloy steel. The Cr content in the interconnector 30 is not particularly limited, but can be 4 mass% or more and 30 mass% or less. The composition of the interconnector 30 may be the same as or different from that of the metal support 10. The composition of the interconnector 30 may be the same as or different from that of the frame 20.
[0077] [First seal portion 40] The first seal portion 40 is disposed between the metal support body 10 and the frame body 20. The first seal portion 40 is joined to both the metal support body 10 and the frame body 20.
[0078] The first seal portion 40 seals the gap between the metal support 10 and the frame 20. This prevents the source gas supplied to the hydrogen electrode 6 and the reducing gas generated in the hydrogen electrode 6 from leaking to the outside through the gap between the metal support 10 and the frame 20. The detailed configuration of the first seal portion 40 will be described later.
[0079] [Second seal portion 50] The second seal portion 50 is disposed between the frame body 20 and the interconnector 30. The second seal portion 50 is joined to each of the frame body 20 and the interconnector 30.
[0080] The second seal portion 50 seals the gap between the frame 20 and the interconnector 30. This prevents the raw material gas supplied to the hydrogen electrode 6 and the reducing gas generated in the hydrogen electrode 6 from leaking to the outside through the gap between the frame 20 and the interconnector 30.
[0081] The configuration of the second seal portion 50 is the same as the configuration of the first seal portion 40, which will be described next, and therefore, in this embodiment, a description of the configuration of the second seal portion 50 will be omitted.
[0082] (Detailed configuration of the first seal portion 40) Fig. 3 is a partially enlarged view of Fig. 2. Fig. 3 shows a cross section of the first seal portion 40. The cross section shown in Fig. 3 is perpendicular to the first main surface 12 of the metal support 10.
[0083] The first seal portion 40 has a first adhesive portion 41 and a second adhesive portion 42. Each of the first adhesive portion 41 and the second adhesive portion 42 is an example of the "adhesive portion" according to the present invention.
[0084] [First adhesive part 41] The first adhesive portion 41 is disposed between the metal support 10 and the frame body 20. The first adhesive portion 41 is sandwiched between the metal support 10 and the frame body 20. The first adhesive portion 41 is formed in an annular shape so as to surround the internal space 3a. The first adhesive portion 41 functions as a seal for sealing the internal space 3a.
[0085] In this embodiment, the first adhesive portion 41 is embedded in a bottomed recess 60 formed between the metal support 10 and the frame 20. The cross section of the bottomed recess 60 is wedge-shaped. The bottomed recess 60 has a deepest part 60a and an opening 60b. The opening 60b opens toward the internal space 3a. The first adhesive portion 41 is exposed to the internal space 3a.
[0086] The first adhesive portion 41 is made of an oxide containing Cr as a main component (hereinafter, abbreviated as "Cr oxide"). This can suppress the diffusion of Cr from the metal support 10 and the frame 20 to the first adhesive portion 41 during the manufacture or operation of the electrolysis cell 1. Even if Cr diffuses from the metal support 10 and the frame 20 to the first adhesive portion 41, the effect on the composition of the first adhesive portion 41 is small, so that the strength of the first adhesive portion 41 can be suppressed from decreasing. Furthermore, since the metal support 10, the frame 20, and the first adhesive portion 41 all contain Cr, the mutual adhesiveness can be improved. Therefore, the adhesiveness between the metal support 10 and the frame 20 can be maintained for a long period of time.
[0087] In this embodiment, "mainly composed of Cr" means that the Cr content is the highest among the metal elements in the Cr oxide when the composition of the Cr oxide constituting the first adhesive portion 41 is analyzed by an energy dispersive spectroscopy (EDS) device. The Cr content is not particularly limited, but can be, for example, 20 mol% to 100 mol%.
[0088] The Cr content in the metal elements in the Cr oxide constituting the first adhesive portion 41 is preferably 50 mol % or more. This makes it possible to significantly suppress the diffusion of Cr contained in the metal support 10 and the frame 20 into the first adhesive portion 41.
[0089] The Cr oxide constituting the first adhesive portion 41 is preferably composed of at least one of chromium oxide and chromium manganese oxide. These oxides have a property that Cr is particularly difficult to diffuse, and therefore the durability of the first adhesive portion 41 can be improved.
[0090] Chromium oxides include Cr2O3, etc. Chromium manganese oxides include MnCr2O4 (spinel), Mn 1,5 Cr 1,5 O4 (spinel) and others.
[0091] The Cr oxide constituting the first adhesive portion 41 is preferably crystalline. This makes it possible to prevent the first adhesive portion 41 from being damaged due to a phase transition of the Cr oxide from amorphous to crystalline even when the electrolysis cell 1 is operated for a long period of time.
[0092] The Cr oxide constituting the first adhesive portion 41 preferably has a spinel or corundum crystal structure. These crystal structures are highly symmetrical, and therefore can improve the thermal stress resistance of the first adhesive portion 41. In addition, Cr oxides having these crystal structures have good bonding properties at the interfaces with the metal support 10 and the frame 20, both of which are made of an alloy containing Cr, and therefore can improve the bonding strength between the first adhesive portion 41 and the metal support 10 and the frame 20, respectively.
[0093] Here, as shown in Fig. 3, the first adhesive portion 41 has metal particles 41a therein. This allows the Cr oxide and the metal particles 41a to be composited, thereby improving the toughness of the first adhesive portion 41. This makes it possible to suppress brittle fracture of the first adhesive portion 41, thereby making it possible to better maintain the adhesion between the metal support 10 and the frame body 20 over a long period of time.
[0094] 3, four metal particles 41a are shown, but the number of metal particles 41a in one cross section is not particularly limited and may be one or more. The metal particles 41a may be entirely embedded in the Cr oxide, or may be partially exposed inside the voids 41b described below. The metal particles 41a are separated from the metal support 10 and the frame 20. However, some of the metal particles 41a may be partially in contact with the metal support 10 or the frame 20.
[0095] The metal particles 41a preferably contain, as a main component, the same element as the main component of at least one of the metal support 10 and the frame 20. This can suppress compositional changes in the first adhesive portion 41 caused by elemental diffusion from the metal support 10 and the frame 20. For example, the metal particles 41a can contain Cr or Fe as a main component. Incidentally, containing as a main component means that the metal particles 41a exhibit the maximum content when subjected to elemental analysis.
[0096] Moreover, it is preferable that the metal particles 41a contain Cr, which can improve the oxidation resistance of the metal particles 41a.
[0097] In the cross section of the first adhesive portion 41, the ratio of the area of the metal particles 41a to the area of the Cr oxide is preferably 5% or more and 30% or less. When the area ratio of the metal particles 41a is 5% or more, the effect of improving toughness due to the presence of the metal particles 41a can be further improved. Also, when the area ratio of the metal particles 41a is 30% or less, a decrease in the rigidity of the first adhesive portion 41 due to the presence of an excessive amount of the metal particles 41a can be suppressed.
[0098] The area ratio of the metal particles 41a is calculated by the following method. First, the cross section of the first adhesive portion 41 along the Z-axis direction is exposed. Next, a backscattered electron image of the cross section of the first adhesive portion 41 is obtained at 10,000 times magnification using an SEM device (FE-SEM JSM-7900F manufactured by JEOL Ltd.). Next, the gray portion (corresponding to Cr oxide), the white portion (corresponding to the metal particles 41a), and the black portion (corresponding to voids) in the backscattered electron image are identified using image analysis software Image-Pro manufactured by MEDIACYBERNETICS. Then, the area ratio of the metal particles 41a is calculated by dividing the total area of the solid phase of the first adhesive portion 41 (i.e., the total area excluding voids).
[0099] It is preferable that the area ratio of the metal particles 41a at the end portions in the planar direction of the first adhesive portion 41 exposed to the internal space 3a is smaller than the area ratio of the metal particles 41a at the center portion in the planar direction. This makes it possible to prevent the metal particles 41a from being embrittled by the reducing gas (H2 in this embodiment) flowing through the internal space 3a. The center portion in the planar direction of the first adhesive portion 41 is a portion located in the center when the first adhesive portion 41 is divided into thirds in the planar direction. The end portions in the planar direction of the first adhesive portion 41 are portions located on the internal space 3a side of the center portion in the planar direction when the first adhesive portion 41 is divided into thirds in the planar direction. The planar direction refers to is perpendicular to the
[0100] In the cross section of the first adhesive portion 41, the average distance between the metal particles 41a is preferably equal to or less than the average thickness of the first adhesive portion 41. This can further improve the effect of improving toughness due to the presence of the metal particles 41a. Note that the thickness of the first adhesive portion 41 is the arithmetic average value of the thicknesses of the first adhesive portion 41 at three points that divide the first adhesive portion 41 into four equal parts in the surface direction.
[0101] The cross-sectional shape of the metal particles 41a is not particularly limited, and may be circular, elliptical, rectangular, polygonal, etc. In the cross section of the first adhesive portion 41, the metal particles 41a may extend along the thickness direction, may extend along the surface direction, or may extend along a direction inclined with respect to both the thickness direction and the surface direction.
[0102] Here, the first adhesive portion 41 preferably has a void 41b therein, as shown in Fig. 3. This allows cracks occurring in the first adhesive portion 41 to be stopped at the void 41b. This makes it possible to prevent the first adhesive portion 41 from undergoing brittle fracture, thereby enabling the adhesion between the metal support 10 and the frame 20 to be maintained for a long period of time.
[0103] In this embodiment, the first adhesive portion 41 has two gaps 41b, but the number of gaps 41b in one cross section is not particularly limited, and may be one or three or more.
[0104] 3, it is preferable that the gap 41b is spaced apart from both the metal support 10 and the frame body 20. This can increase the adhesion area between the first adhesive portion 41 and the metal support 10 and between the first adhesive portion 41 and the frame body 20, and therefore can improve the adhesion between the first adhesive portion 41 and the metal support 10 and between the first adhesive portion 41 and the frame body 20.
[0105] The voids 41b may extend along a thickness direction parallel to the Z-axis direction. This allows the voids 41b to stop cracks extending along a surface direction perpendicular to the thickness direction over a wide area. The thickness direction is a direction perpendicular to the first main surface 12 of the metal support 10. Extending along the thickness direction means that the thickness of the voids 41b in the thickness direction is greater than the width of the voids 41b in the surface direction.
[0106] The voids 41b may extend along a surface direction perpendicular to the Z-axis direction. This allows the voids 41b to stop cracks extending along the thickness direction over a wide area. Note that extending along the surface direction means that the thickness of the voids 41b in the thickness direction is smaller than the width of the voids 41b in the surface direction.
[0107] The voids 41b may extend in a direction inclined with respect to both the thickness direction and the surface direction. This allows the voids 41b to stop both cracks extending in the thickness direction and cracks extending in the surface direction in a well-balanced manner. In this case, the thickness of the voids 41b in the thickness direction may be approximately the same as the width of the voids 41b in the surface direction.
[0108] It is preferable that the void 41b is located in the center in the thickness direction of the first adhesive portion 41. This can reduce the difference in strength of the first adhesive portion 41 on the metal support 10 side and the frame 20 side of the void 41b, thereby preventing a decrease in the mechanical reliability of the first adhesive portion 41. It is more preferable that the void 41b is entirely contained in the center in the thickness direction of the first adhesive portion 41. Note that the center in the thickness direction is a portion located in the center when the first adhesive portion 41 is divided into three equal parts on a virtual line that is parallel to the thickness direction and passes through the void 41b.
[0109] The thickness of the void 41b is preferably 3 / 4 or less of the thickness of the first adhesive portion 41. This can prevent a decrease in the strength of the first adhesive portion 41 on the metal support 10 side and the frame 20 side of the void 41b, and therefore can prevent the first adhesive portion 41 from peeling off from the metal support 10 and the frame 20. The thickness of the first adhesive portion 41 is the sum of the shortest distance between the void 41b and the metal support 10 in the thickness direction, the shortest distance of the void 41b in the thickness direction, and the thickness of the void 41b in the thickness direction.
[0110] The ratio of the thickness of the voids 41b to the thickness of at least one of the metal support 10 and the frame 20 is preferably 20 or more and 500 or less. When the thickness ratio is 20 or more, the effect of stopping cracks caused by the voids 41b can be sufficiently exhibited. Also, when the thickness ratio is 500 or less, a decrease in the mechanical reliability of the first adhesive portion 41 due to the presence of the voids 41b can be suppressed.
[0111] In the cross section of the first adhesive portion 41, the ratio of the area of the voids 41b to the area of the first adhesive portion 41 is preferably 5% or more and 30% or less. When the area ratio of the voids 41b is 5% or more, the effect of stopping cracks caused by the voids 41b can be sufficiently exhibited. Also, when the area ratio of the voids 41b is 30% or less, a decrease in the mechanical reliability of the first adhesive portion 41 due to the presence of the voids 41b can be suppressed.
[0112] The area ratio of the voids 41b is calculated by the following method. First, a cross section of the first adhesive portion 41 along the Z-axis direction is exposed. Next, a backscattered electron image of the cross section of the first adhesive portion 41 is obtained at 10,000 times magnification using an SEM device (FE-SEM JSM-7900F manufactured by JEOL Ltd.). Next, a portion displayed in black in the backscattered electron image (corresponding to the voids 41b) is identified using image analysis software Image-Pro manufactured by MEDIACYBERNETICS. Then, the area ratio of the voids 41b is calculated by dividing the total area of the backscattered electron images of the first adhesive portion 41 by the total area of the backscattered electron images of the first adhesive portion 41.
[0113] The area ratio of the voids 41b at the end portions in the planar direction exposed to the internal space 3a of the first adhesive portion 41 is preferably smaller than the area ratio of the voids 41b at the center portion in the planar direction. This makes it possible to prevent the reducing gas (H2 in this embodiment) flowing through the internal space 3a from entering the voids 41b, thereby further improving the sealing performance of the first adhesive portion 41. The center portion in the planar direction of the first adhesive portion 41 is a portion located at the center when the first adhesive portion 41 is divided into three equal parts on a virtual line that is parallel to the planar direction and passes through the voids 41b. The end portions in the planar direction of the first adhesive portion 41 are portions located on the virtual line on the side of the internal space 3a of the center portion in the planar direction.
[0114] The first adhesive portion 41 can be formed by applying a paste containing Cr oxide and metal particles onto at least one of the surfaces of the metal support 10 and the frame 20, and then performing a heat treatment while the metal support 10 and the frame 20 are in close contact with each other. The conditions for the heat treatment can be set as appropriate, and can be, for example, 600° C. or higher and 1100° C. or lower, and 0.5 hours or higher and 24 hours or lower. When voids 41b are to be formed in the first adhesive portion 41, a pore-forming material can be appropriately added to the paste.
[0115] [Second adhesive part 42] The second adhesive portion 42 is disposed between the metal support 10 and the frame body 20. The second adhesive portion 42 is sandwiched between the metal support 10 and the frame body 20. The second adhesive portion 42 is disposed on the opposite side of the internal space 3a with respect to the first adhesive portion 41. The second adhesive portion 42 is formed in an annular shape so as to surround the first adhesive portion 41. The second adhesive portion 42 functions as a seal for sealing the internal space 3a.
[0116] The second adhesive portion 42 is separated from the first adhesive portion 41 in the surface direction. The metal support 10 and the frame body 20 are in close contact with or integrated with each other between the first adhesive portion 41 and the second adhesive portion 42. In order to improve the electrical connectivity between the metal support 10 and the frame body 20, it is preferable that they are integrated by welding or brazing.
[0117] In this embodiment, the second adhesive portion 42 is embedded in a bottomed recess 70 formed between the metal support 10 and the frame body 20. The cross section of the bottomed recess 70 is wedge-shaped. The bottomed recess 70 has a deepest part 70a and an opening 70b. The opening 70b opens toward the external space 3b. The second adhesive portion 42 is exposed to the external space 3b.
[0118] The second adhesive portion 42 is made of Cr oxide. This can suppress the diffusion of Cr from the metal support 10 and the frame 20 to the second adhesive portion 42 during the manufacture or operation of the electrolysis cell 1. Even if Cr diffuses from the metal support 10 and the frame 20 to the second adhesive portion 42, the effect on the composition of the second adhesive portion 42 is small, so that the strength of the second adhesive portion 42 can be suppressed from decreasing. Furthermore, since the metal support 10, the frame 20, and the second adhesive portion 42 all contain Cr, the mutual adhesion can be improved. Therefore, the adhesion between the metal support 10 and the frame 20 can be maintained for a long period of time.
[0119] The Cr content of the metal elements in the Cr oxide constituting the second adhesive portion 42 can be, for example, 20 mol % or more and 100 mol % or less. The Cr content is preferably 50 mol % or more. This significantly suppresses the diffusion of Cr contained in the metal support 10 and the frame 20 into the second adhesive portion 42.
[0120] The Cr oxide constituting the second adhesive portion 42 is preferably composed of at least one of chromium oxide and chromium manganese oxide. These oxides have a property that Cr is particularly difficult to diffuse, and therefore the durability of the second adhesive portion 42 can be improved.
[0121] The Cr oxide constituting the second adhesive portion 42 is preferably crystalline. This makes it possible to prevent the second adhesive portion 42 from being damaged due to a phase transition of the Cr oxide from amorphous to crystalline even when the electrolysis cell 1 is operated for a long period of time.
[0122] The Cr oxide constituting the second adhesive portion 42 preferably has a spinel or corundum crystal structure, which can improve the thermal stress resistance of the second adhesive portion 42 and can also improve the bonding strength between the second adhesive portion 42 and the metal support 10 and between the second adhesive portion 42 and the frame 20.
[0123] Here, as shown in Fig. 3, the second adhesive portion 42 has metal particles 42a therein. This allows the Cr oxide and the metal particles 42a to be composited, thereby improving the toughness of the second adhesive portion 42. This makes it possible to suppress brittle fracture of the second adhesive portion 42, thereby making it possible to better maintain the adhesion between the metal support 10 and the frame 20 over a long period of time.
[0124] In FIG. 3, three metal particles 42a are shown, but the number of metal particles 42a in one cross section is not particularly limited and may be one or more. The metal particles 42a may be entirely embedded in the Cr oxide, or may be partially exposed inside the voids 42b described later. The metal particles 42a are separated from the metal support 10 and the frame 20. However, some of the metal particles 42a may be partially in contact with the metal support 10 or the frame 20.
[0125] The metal particles 42a preferably contain, as a main component, the same element as the main component of at least one of the metal support 10 and the frame body 20. This makes it possible to suppress a change in composition of the second adhesive portion 42 due to element diffusion from the metal support 10 and the frame body 20. For example, the metal particles 42a can contain Cr or Fe as a main component.
[0126] Moreover, the metal particles 42a preferably contain Cr, which can improve the oxidation resistance of the metal particles 42a.
[0127] In the cross section of the second adhesive portion 42, the ratio of the area of the metal particles 42a to the area of the Cr oxide is preferably 5% or more and 30% or less. When the area ratio of the metal particles 42a is 5% or more, the effect of improving toughness due to the presence of the metal particles 42a can be further improved. Furthermore, when the area ratio of the metal particles 42a is 30% or less, a decrease in rigidity of the second adhesive portion 42 due to the presence of an excessive amount of the metal particles 42a can be suppressed. The area ratio of the metal particles 42a is calculated by the same method as that of the metal particles 41a described above.
[0128] The area ratio of the metal particles 42a at the end portions in the planar direction of the second adhesive portion 42 exposed to the external space 3b is preferably smaller than the area ratio of the metal particles 42a at the center portion in the planar direction. This makes it possible to prevent the metal particles 42a from being oxidized by the oxidant gas (O2 in this embodiment) flowing through the external space 3b. The center portion in the planar direction of the second adhesive portion 42 is a portion located at the center when the second adhesive portion 42 is divided into thirds in the planar direction. The end portions in the planar direction of the second adhesive portion 42 are portions located on the external space 3b side of the center portion in the planar direction when the second adhesive portion 42 is divided into thirds in the planar direction.
[0129] In the cross section of the second adhesive portion 42, the average distance between the metal particles 42a is preferably equal to or less than the average thickness of the second adhesive portion 42. This can further improve the effect of improving toughness due to the presence of the metal particles 42a. Note that the thickness of the second adhesive portion 42 is the arithmetic average value of the thicknesses of the second adhesive portion 42 at three locations that divide the second adhesive portion 42 into four equal parts in the surface direction.
[0130] The cross-sectional shape of the metal particles 42a is not particularly limited, and may be circular, elliptical, rectangular, polygonal, etc. In the cross section of the second adhesive portion 42, the metal particles 42a may extend along the thickness direction, may extend along the surface direction, or may extend along a direction inclined with respect to both the thickness direction and the surface direction.
[0131] Here, the second adhesive portion 42 preferably has a void 42b therein, as shown in Fig. 3. This allows cracks occurring in the second adhesive portion 42 to be stopped at the void 42b. This makes it possible to prevent the second adhesive portion 42 from undergoing brittle fracture, thereby enabling the adhesion between the metal support 10 and the frame 20 to be better maintained over a long period of time.
[0132] In this embodiment, the second adhesive portion 42 has one gap 42b, but the number of gaps 42b in one cross section is not particularly limited, and may be two or more.
[0133] 3, the gap 42b is preferably located away from both the metal support 10 and the frame 20. This can improve the adhesiveness between the second adhesive portion 42 and both the metal support 10 and the frame 20.
[0134] The voids 42b may extend along the thickness direction parallel to the Z-axis direction, thereby making it possible for the voids 42b to stop cracks extending along the surface direction over a wide area.
[0135] The voids 42b may extend along a surface direction perpendicular to the Z-axis direction, thereby making it possible for the voids 42b to stop cracks extending along the thickness direction over a wide area.
[0136] The voids 42b may extend in a direction inclined with respect to both the thickness direction and the surface direction, thereby allowing the voids 42b to stop both cracks extending in the thickness direction and cracks extending in the surface direction in a well-balanced manner.
[0137] The void 42b is preferably located in the center in the thickness direction of the second adhesive portion 42. This reduces the difference in strength of the second adhesive portion 42 on the metal support 10 side and the frame 20 side of the void 42b, thereby preventing a decrease in the mechanical reliability of the second adhesive portion 42. It is more preferable that the void 42b is entirely located in the center in the thickness direction of the second adhesive portion 42.
[0138] The thickness of the gap 42b is preferably 3 / 4 or less of the thickness of the second adhesive portion 42. This makes it possible to prevent the second adhesive portion 42 from peeling off from the metal support 10 and the frame 20, respectively.
[0139] The ratio of the thickness of the voids 42b to the thickness of at least one of the metal support 10 and the frame 20 is preferably equal to or greater than 20 and equal to or less than 500. This makes it possible to fully exert the effect of stopping cracks caused by the voids 42b and to suppress a decrease in the mechanical reliability of the second adhesive portion 42.
[0140] In the cross section of the second adhesive portion 42, the ratio of the area of the voids 42b to the area of the second adhesive portion 42 is preferably 5% or more and 30% or less. This makes it possible to fully exert the effect of stopping cracks caused by the voids 42b and to suppress a decrease in the mechanical reliability of the second adhesive portion 42.
[0141] It is preferable that the area ratio of the gaps 42b at the end portions in the planar direction of the second adhesive portion 42 exposed to the external space 3b is smaller than the area ratio of the gaps 42b at the center portion in the planar direction. This can prevent the oxidant gas (O2 in this embodiment) flowing through the external space 3b from entering the gaps 42b, thereby further improving the sealing performance of the second adhesive portion 42. Note that the center portion in the planar direction of the second adhesive portion 42 is a portion located at the center when the second adhesive portion 42 is divided into three equal parts on a virtual line that is parallel to the planar direction and passes through the gaps 42b. The end portions in the planar direction of the second adhesive portion 42 are portions located on the virtual line on the external space 3b side of the center portion in the planar direction.
[0142] The second adhesive portion 42 can be formed by applying a paste containing Cr oxide and metal particles onto at least one of the surfaces of the metal support 10 and the frame 20, and then performing a heat treatment with the metal support 10 and the frame 20 in close contact with each other. The conditions for the heat treatment can be set as appropriate, for example, at 600°C or higher and 1100°C or lower, and for 0.5 hours or higher and 24 hours or lower. When voids 42b are formed in the second adhesive portion 42, a pore-forming material may be appropriately added to the paste. The second adhesive portion 42 may be formed simultaneously with the first adhesive portion 41.
[0143] 2. Second embodiment
[0144] (Electrolysis cell 1) 4 is a cross-sectional view of an electrolysis cell 1a according to the second embodiment. The electrolysis cell 1a is an example of the "metal-supported electrochemical cell" according to the present invention.
[0145] The electrolytic cell 1a according to the second embodiment differs from the electrolytic cell 1 according to the first embodiment in that the interconnector 30 has an embossed portion 31 and a debossed portion 32, and that the chromium alloy container 3 has a third adhesive portion 43. The following mainly describes these differences.
[0146] In this embodiment, one of the metal support 10 and the interconnector 30 is an example of the "first alloy member" according to the present invention, and the other is an example of the "second alloy member" according to the present invention. Also, the third adhesive portion 43 is an example of the "adhesive portion" according to the present invention.
[0147] As shown in Fig. 4, the interconnector 30 has a plurality of embossed portions 31 and a plurality of debossed portions 32. Although two embossed portions 31 and three debossed portions 32 are illustrated in Fig. 4, the numbers of the embossed portions 31 and the debossed portions 32 can be changed as appropriate.
[0148] The embossed portion 31 abuts against the second main surface 13 of the metal support 10. As a result, the metal support 10 is supported by the interconnector 30, and thus bending of the metal support 10 is suppressed. Note that the embossed portion 31 only needs to abut against the metal support 10, and does not need to be fixed to the metal support 10.
[0149] The debossed portion 32 protrudes toward the side opposite to the metal support 10. The debossed portion 32 abuts against an external power source or another electrolytic cell.
[0150] The third adhesive portion 43 adheres the embossed portion 31 to the metal support 10. The third adhesive portion 43 is disposed around the tip portion of the embossed portion 31. The tip portion of the embossed portion 31 refers to the portion of the embossed portion 31 that abuts against the metal support 10. The third adhesive portion 43 is preferably formed in a ring shape so as to surround the tip portion of the embossed portion 31. This can improve the adhesion between the embossed portion 31 and the metal support 10.
[0151] Here, Fig. 5 is a partially enlarged view of Fig. 4. Fig. 5 illustrates a cross section of the third adhesive portion 43. The cross section illustrated in Fig. 5 is perpendicular to the second main surface 13 of the metal support 10.
[0152] The third adhesive portion 43 is disposed between the metal support 10 and the embossed portion 31. The third adhesive portion 43 is sandwiched between the metal support 10 and the embossed portion 31. The third adhesive portion 43 is disposed on the metal support 10, and is formed in an annular shape so as to surround the tip portion of the embossed portion 31.
[0153] In this embodiment, the third adhesive portion 43 is embedded in a bottomed recess 80 formed between the metal support 10 and the embossed portion 31. The cross section of the bottomed recess 80 is wedge-shaped. The bottomed recess 80 has a deepest part 80a and an opening 80b. The opening 80b opens toward the internal space 3a. The third adhesive portion 43 is exposed to the internal space 3a.
[0154] The third adhesive portion 43 is made of Cr oxide. This can suppress the diffusion of Cr from the metal support 10 and the embossed portion 31 to the third adhesive portion 43 during the manufacture or operation of the electrolysis cell 1a. Even if Cr diffuses from the metal support 10 and the embossed portion 31 to the third adhesive portion 43, the effect on the composition of the third adhesive portion 43 is small, so that the strength of the third adhesive portion 43 can be suppressed from decreasing. Furthermore, since the metal support 10, the embossed portion 31, and the third adhesive portion 43 all contain Cr, the mutual adhesiveness can be improved. Therefore, the adhesiveness between the metal support 10 and the embossed portion 31 can be maintained for a long period of time.
[0155] The Cr content of the metal elements in the Cr oxide constituting the third adhesive portion 43 can be, for example, 20 mol % or more and 100 mol % or less. The Cr content is preferably 50 mol % or more. This significantly prevents the Cr contained in the metal support 10 and the embossed portion 31 from diffusing into the third adhesive portion 43.
[0156] The Cr oxide constituting the third adhesive portion 43 is preferably composed of at least one of chromium oxide and chromium manganese oxide. These oxides have a property that Cr is particularly difficult to diffuse, and therefore the durability of the third adhesive portion 43 can be improved.
[0157] The Cr oxide constituting the third adhesive portion 43 is preferably crystalline. This makes it possible to prevent the third adhesive portion 43 from being damaged due to a phase transition of the Cr oxide from amorphous to crystalline even when the electrolysis cell 1a is operated for a long period of time.
[0158] The Cr oxide constituting the third adhesive portion 43 preferably has a spinel or corundum crystal structure, which can improve the thermal stress resistance of the third adhesive portion 43 and can also improve the bonding strength between the third adhesive portion 43 and the metal support 10 and between the third adhesive portion 43 and the interconnector 30.
[0159] 5, the third adhesive portion 43 has metal particles 43a therein. This allows the Cr oxide and the metal particles 43a to be composited, improving the toughness of the third adhesive portion 43. This makes it possible to suppress brittle fracture of the third adhesive portion 43, thereby enabling the adhesion between the metal support 10 and the frame 20 to be maintained for a long period of time.
[0160] 5 shows four metal particles 43a, the number of metal particles 43a in one cross section is not particularly limited and may be one or more. The metal particles 43a may be entirely embedded in the Cr oxide, or may be partially exposed inside the voids 43b described later. The metal particles 43a are separated from the metal support 10 and the interconnector 30. However, some of the metal particles 43a may be in partial contact with the metal support 10 and the interconnector 30.
[0161] The metal particles 43a preferably contain, as a main component, the same element as the main component of at least one of the metal support 10 and the interconnector 30. This makes it possible to suppress a change in composition of the third adhesive portion 43 due to element diffusion from the metal support 10 and the interconnector 30. For example, the metal particles 43a can contain Cr or Fe as a main component.
[0162] Moreover, the metal particles 43a preferably contain Cr, which can improve the oxidation resistance of the metal particles 43a.
[0163] In the cross section of the third adhesive portion 43, the ratio of the area of the metal particles 43a to the area of the Cr oxide is preferably 5% or more and 30% or less. When the area ratio of the metal particles 43a is 5% or more, the effect of improving toughness due to the presence of the metal particles 43a can be further improved. Furthermore, when the area ratio of the metal particles 43a is 30% or less, the decrease in rigidity of the third adhesive portion 43 due to the presence of an excessive amount of the metal particles 43a can be suppressed. The area ratio of the metal particles 43a is calculated by the same method as that of the metal particles 41a described above.
[0164] The area ratio of the metal particles 43a at the end portions in the planar direction exposed to the internal space 3a of the third adhesive portion 43 is preferably smaller than the area ratio of the metal particles 43a at the center portion in the planar direction. This can prevent the metal particles 43a from being embrittled by the reducing gas (H2 in this embodiment) flowing through the internal space 3a. The center portion in the planar direction of the third adhesive portion 43 is a portion located at the center when the third adhesive portion 43 is divided into three equal parts in the planar direction. The end portions in the planar direction of the third adhesive portion 43 are portions located on the internal space 3a side of the center portion in the planar direction when the third adhesive portion 43 is divided into three equal parts in the planar direction.
[0165] In the cross section of the third adhesive portion 43, the average distance between the metal particles 43a is preferably equal to or less than the average thickness of the third adhesive portion 43. This can further improve the effect of improving toughness due to the presence of the metal particles 43a. Note that the thickness of the third adhesive portion 43 is the arithmetic average value of the thicknesses of the third adhesive portion 43 at three points that divide the third adhesive portion 43 into four equal parts in the surface direction.
[0166] The cross-sectional shape of the metal particles 43a is not particularly limited, and may be circular, elliptical, rectangular, polygonal, etc. In the cross section of the third adhesive portion 43, the metal particles 43a may extend along the thickness direction, may extend along the surface direction, or may extend along a direction inclined with respect to both the thickness direction and the surface direction.
[0167] Here, it is preferable that the third adhesive portion 43 has a void 43b therein, as shown in Fig. 5. This makes it possible to stop cracks occurring in the third adhesive portion 43 at the void 43b. This makes it possible to suppress brittle fracture of the third adhesive portion 43, so that the adhesion between the metal support 10 and the interconnector 30 can be maintained for a long period of time.
[0168] In this embodiment, the third adhesive portion 43 has one gap 43b, but the number of gaps 43b in one cross section is not particularly limited, and may be two or more.
[0169] 5, the gap 43b is preferably located away from both the metal support 10 and the interconnector 30. This can improve the adhesion between the third adhesive portion 43 and both the metal support 10 and the interconnector 30.
[0170] The voids 43b may extend along the thickness direction parallel to the Z-axis direction, thereby making it possible for cracks extending along the surface direction to be stopped over a wide area by the voids 43b.
[0171] The voids 43b may extend along a surface direction perpendicular to the Z-axis direction, thereby making it possible for cracks extending along the thickness direction to be stopped over a wide area by the voids 43b.
[0172] The voids 43b may extend in a direction inclined with respect to both the thickness direction and the surface direction, thereby allowing the voids 43b to stop both cracks extending in the thickness direction and cracks extending in the surface direction in a well-balanced manner.
[0173] The void 43b is preferably located in the center in the thickness direction of the third adhesive portion 43. This reduces the difference in strength of the third adhesive portion 43 on the metal support 10 side and the interconnector 30 side of the void 43b, thereby suppressing a decrease in the mechanical reliability of the third adhesive portion 43. It is more preferable that the void 43b is entirely contained in the center in the thickness direction of the third adhesive portion 43.
[0174] The thickness of the gap 43b is preferably 3 / 4 or less of the thickness of the third adhesive portion 43. This can prevent the third adhesive portion 43 from peeling off from the metal support 10 and the interconnector 30, respectively.
[0175] The ratio of the thickness of the voids 43b to the thickness of at least one of the metal support 10 and the interconnector 30 is preferably equal to or greater than 20 and equal to or less than 500. This makes it possible to fully exert the effect of stopping cracks caused by the voids 43b and to suppress a decrease in the mechanical reliability of the third adhesive portion 43.
[0176] In the cross section of the third adhesive portion 43, the ratio of the area of the voids 43b to the area of the third adhesive portion 43 is preferably 5% or more and 30% or less. This makes it possible to fully exert the effect of stopping cracks caused by the voids 43b and to suppress a decrease in the mechanical reliability of the third adhesive portion 43.
[0177] It is preferable that the area ratio of the gap 43b at the end portion in the planar direction exposed to the internal space 3a of the third adhesive portion 43 is smaller than the area ratio of the gap 43b at the center portion in the planar direction. This makes it possible to prevent the oxidizing gas (O2 in this embodiment) flowing through the internal space 3a from entering the gap 43b, thereby further improving the sealing property of the third adhesive portion 43.
[0178] The third adhesive portion 43 can be formed by applying a paste containing Cr oxide and metal particles onto at least one of the surfaces of the metal support 10 and the embossed portion 31, and then performing a heat treatment while the metal support 10 and the embossed portion 31 are in close contact with each other. The conditions for the heat treatment can be set appropriately, and can be, for example, 800°C to 1100°C and 0.5 hours to 24 hours. In addition, when forming voids 43b in the third adhesive portion 43, a pore-forming material can be appropriately added to the paste. In addition, the third adhesive portion 43 may be formed simultaneously with the first and second adhesive portions 41 and 42.
[0179] (Modification of the embodiment) Although the embodiments of the present invention have been described above, the present invention is not limited to these, and various modifications are possible without departing from the spirit of the present invention.
[0180] [Variation 1] In the above first and second embodiments, the frame 20 and the interconnector 30 are separate members, but the frame 20 and the interconnector 30 may be an integral member. In this case, the chromium alloy container 3 does not include the second seal portion 50.
[0181] [Variation 2] In the first and second embodiments, the metal support 10 and the frame 20 are separate members, but the metal support 10 and the frame 20 may be an integral member. In this case, the chromium alloy container 3 does not include the first seal portion 40.
[0182] [Variation 3] In the first and second embodiments, the first adhesive portion 41 has a single-layer structure, but is not limited thereto. The first adhesive portion 41 may have a multi-layer structure including two or more layers each composed of Cr oxides having different compositions.
[0183] [Variation 4] In the first and second embodiments, the second adhesive portion 42 has a single-layer structure, but is not limited thereto. The second adhesive portion 42 may have a multi-layer structure including two or more layers each composed of Cr oxides having different compositions.
[0184] [Variation 5] In the second embodiment, the third adhesive portion 43 has a single-layer structure, but is not limited thereto. The third adhesive portion 43 may have a multi-layer structure including two or more layers each composed of Cr oxides having different compositions.
[0185] [Variation 6] In the above first and second embodiments, the first seal portion 40 has the first adhesive portion 41 and the second adhesive portion 42, but it may have only one of the first adhesive portion 41 and the second adhesive portion 42.
[0186] In addition, the second seal portion 50 has the same configuration as the first seal portion 40, but may have a different configuration from the first seal portion 40. The second seal portion 50 may have only one of the first adhesive portion 41 and the second adhesive portion 42.
[0187] [Variation 7] In the above first and second embodiments, the metal support 10 and the frame body 20 are in close contact with or integrated with each other between the first adhesive portion 41 and the second adhesive portion 42, but this is not limited thereto. The metal support 10 and the frame body 20 do not have to be in close contact with or integrated with each other.
[0188] [Variation 8] In the above embodiment, an electrolytic cell has been described as an example of an electrochemical cell, but the electrochemical cell is not limited to an electrolytic cell. An electrochemical cell is a general term for an element in which a pair of electrodes are arranged so that an electromotive force is generated from an overall oxidation-reduction reaction in order to convert electrical energy into chemical energy, and an element for converting chemical energy into electrical energy. Therefore, the electrochemical cell includes, for example, a fuel cell that uses oxide ions or protons as a carrier.
[0189] [Variation 9] In the above embodiment, the chromium alloy container according to the present invention is applied to an electrochemical cell, but the chromium alloy container can be used for various purposes. For example, the chromium alloy container can be used as a methanation reactor for synthesizing methane from hydrogen and carbon dioxide. EXAMPLES
[0190] The following describes examples of the chromium alloy container according to the present invention, but the present invention is not limited to the following examples.
[0191] (Sample No. 1-9) Chromium alloy containers 3 (see FIG. 3) according to Samples No. 1 to 9 were fabricated as follows.
[0192] First, a paste containing Cr2O3 and metal particles (specifically, SUS430 particles) was applied to the outer periphery of the second main surface 13 of the metal support 10, and then the frame 20 was placed on the paste to produce a laminate. At this time, the ratio of the area of the metal particles 41a to the area of the Cr oxide was changed by changing the amount of metal particles added, as shown in Table 1.
[0193] Next, the metal support 10 and the frame 20 were lap-welded to be integrated with each other between the first adhesive portion 41 and the second adhesive portion 42.
[0194] Next, the laminate was subjected to a heat treatment (1000°C, 1 hour) to form a first adhesive portion 41 having metal particles 41a therein and a second adhesive portion 42 having metal particles 42a therein from the paste. In this way, a chromium alloy container 3 having the first and second adhesive portions 41 and 42 was completed.
[0195] Next, a heat endurance test was carried out by subjecting the chromium alloy container 3 to a heat treatment (800° C., 1000 hours).
[0196] Next, the chromium alloy container 3 was cut along the thickness direction to expose a cross section of the first adhesive portion 41 along the thickness direction.
[0197] Next, as described in the above embodiment, the ratio of the area of the metal particles 41a to the area of the Cr oxide was calculated in the cross section of the first adhesive portion 41. The calculated area ratios are shown in Table 1.
[0198] Next, the cross section of the first adhesive portion 41 was observed with an SEM (5000x magnification) to measure the length of the largest crack that occurred inside the first adhesive portion 41. The largest crack is the crack with the longest linear distance between both ends among all cracks observed in any five fields of view. If the entire crack did not fit within the observation field of view, the crack length was measured by acquiring multiple images while sliding the field of view as appropriate and stitching them together. The length of the largest crack is shown in Table 1.
[0199] Next, the cross section of the first adhesive portion 41 was observed with an SEM (5000x) to check whether the first adhesive portion 41 had locally peeled off from the metal support 10 and the frame 20 near the metal particles 41a. The peeling confirmation results are shown in Table 1.
[0200] [Table 1]
[0201] As shown in Table 1, in samples Nos. 1 to 5 in which the ratio of the area of the metal particles 41a to the area of the Cr oxide was 5% or more and 30% or less, the maximum crack length after the heat endurance test was significantly shortened, and peeling of the first adhesive portion 41 from the metal support 10 and the frame 20 was suppressed. This shows that by setting the ratio of the area of the metal particles 41a to the area of the Cr oxide to 5% or more and 30% or less, the toughness of the first adhesive portion 41 can be improved and a decrease in rigidity can be suppressed.
[0202] Although not shown in Table 1, the same results as those of the first adhesive portion 41 were obtained in the second adhesive portion 42.
[0203] (Sample No. 10-17) Chromium alloy containers 3 (see FIG. 3) according to Samples No. 10 to 17 were fabricated as follows.
[0204] First, a paste containing Cr2O3 and metal particles (specifically, SUS430 particles) was applied to the outer periphery of the second main surface 13 of the metal support 10, and then the frame 20 was placed on the paste to produce a laminate. At this time, the ratio of the average distance between the metal particles 41a to the average thickness of the first adhesive portion 41 was changed by changing the amount of metal particles added, as shown in Table 2.
[0205] Next, the metal support 10 and the frame 20 were lap-welded to be integrated with each other between the first adhesive portion 41 and the second adhesive portion 42.
[0206] Next, the laminate was subjected to a heat treatment (1000°C, 1 hour) to form a first adhesive portion 41 having metal particles 41a therein and a second adhesive portion 42 having metal particles 42a therein from the paste. In this way, a chromium alloy container 3 having the first and second adhesive portions 41 and 42 was completed.
[0207] Next, a heat endurance test was carried out by subjecting the chromium alloy container 3 to a heat treatment (800° C., 1000 hours).
[0208] Next, the chromium alloy container 3 was cut along the thickness direction to expose a cross section of the first adhesive portion 41 along the thickness direction.
[0209] Next, the cross section of the first adhesive portion 41 was observed with an SEM (at a magnification capable of measuring the thickness of the first adhesive portion 41 in one field of view) to calculate the average thickness of the first adhesive portion 41 at three locations that divide the first adhesive portion 41 into four equal parts in the surface direction. In addition, the average distance between all of the metal particles 41a observed in the three SEM images used to calculate the average thickness was calculated. Then, the ratio of the average distance between the metal particles 41a to the average thickness of the first adhesive portion 41 was calculated. The ratio is shown in Table 2.
[0210] Next, the cross section of the first adhesive portion 41 was observed with an SEM (5000x) to measure the length of the maximum crack that occurred inside the first adhesive portion 41. Then, the ratio of the length of the maximum crack to the average thickness of the first adhesive portion 41 was calculated. The ratio is shown in Table 2.
[0211] [Table 2]
[0212] As shown in Table 2, in samples Nos. 10 to 14 in which the ratio of the average distance between the metal particles 41a to the average thickness of the first adhesive portion 41 was 1.0 or less, the maximum crack length after the heat durability test was significantly shortened. This shows that the toughness of the first adhesive portion 41 can be improved by setting the average distance between the metal particles 41a to be equal to or less than the average thickness of the first adhesive portion 41.
[0213] Although not shown in Table 2, the same results as those of the first adhesive portion 41 were obtained in the second adhesive portion 42.
[0214] (Sample No. 18~24) Chromium alloy containers according to Samples Nos. 18 to 24 were produced as follows.
[0215] First, a paste containing at least one of Cr2O3 and Mn3O4 and metal particles was applied to the outer periphery of the second main surface 13 of the metal support 10, and then a frame 20 was placed on the paste to produce a laminate. At this time, the amount of Cr2O3 and Mn3O4 charged was changed to change the Cr content in the metal elements in the Cr oxide that constitutes the adhesive joint, as shown in Table 3. However, the amount and particle size of the metal particles were the same for all samples.
[0216] Next, the laminate was subjected to a heat treatment (1000°C, 1 hour) to form an adhesive part having metal particles therein from the paste. This resulted in a chromium alloy container having an adhesive part. In this example, the metal support 10 and the frame 20 were not welded or brazed.
[0217] Next, the composition of the Cr oxide that constitutes the bonded joint was analyzed with an EDS device to measure the Cr content in the metal elements in the Cr oxide. The Cr content at this time is shown in Table 3 as the "Cr content before heat durability test."
[0218] Next, a thermal endurance test was carried out by subjecting the chromium alloy container to a heat treatment (800°C, 1000 hours).
[0219] Next, the composition of the Cr oxide that constituted the bonded joint was analyzed with an EDS device to measure the Cr content of the metal elements in the Cr oxide again. The Cr content at this time is shown in Table 3 as the "Cr content after heat durability test."
[0220] [Table 3]
[0221] As shown in Table 3, in samples No. 20 to No. 23 in which the Cr content before the thermal endurance test was set to 50 mol% or more, the change in Cr content before and after the thermal endurance test was significantly reduced. This shows that by setting the Cr content of metal elements in the Cr oxide constituting the adhesive joint to 50 mol% or more, it is possible to significantly prevent the Cr contained in the metal support 10 and the frame 20 from diffusing into the adhesive joint. [Explanation of symbols]
[0222] 1,1a Electrolysis cell 2 Cell body 3. Chromium alloy container 3a Interior space 6 Hydrogen electrode 7 Electrolytes 8. Reaction prevention layer 9 Oxygen electrode 10 Metal support 11 Supply hole 12 First main surface 13 Second main surface 20 Frame 30 Interconnector 31 Embossed section 40 First seal part 41 1st adhesive part 42 2nd adhesive part 43 3rd adhesive part 41a,42a,43a Metal particles 41b,42b,43b void
Claims
1. A chromium alloy container having an internal space, A first alloy member made of an alloy containing chromium; A second alloy member made of an alloy containing chromium; an adhesive portion that bonds the first alloy member and the second alloy member; Equipped with The adhesive portion is composed of an oxide mainly composed of chromium and metal particles at least partially embedded in the oxide. Chromium alloy container.
2. The metal particles contain, as a main component, the same element as a main component of at least one of the first alloy member and the second alloy member.
2. The chromium alloy container according to claim 1.
3. The metal particles contain chromium.
3. The chromium alloy container according to claim 1 or 2.
4. In a cross section of the adhesive joint, the ratio of the area of the metal particles to the area of the oxide is 5% or more and 30% or less.
2. The chromium alloy container according to claim 1.
5. In the cross section of the adhesive joint, the average distance between the metal particles is equal to or less than the average thickness of the adhesive joint.
2. The chromium alloy container according to claim 1.
6. The adhesive portion has a void therein.
2. The chromium alloy container according to claim 1.
7. The chromium content in the metal elements in the oxide is 50 mol% or more.
2. The chromium alloy container according to claim 1.
8. The oxide is composed of at least one of chromium oxide and chromium manganese oxide.
2. The chromium alloy container according to claim 1.
9. The oxide is crystalline.
2. The chromium alloy container according to claim 1.
10. The oxide has a spinel or corundum type crystal structure.
10. The chromium alloy container of claim 9.
11. The adhesive portion is a seal for sealing the internal space.
2. The chromium alloy container according to claim 1.
12. The second alloy member has an embossed portion in contact with the first alloy member, The adhesive portion adheres the embossed portion to the first alloy member.
2. The chromium alloy container according to claim 1.
13. The chromium alloy container according to claim 1 ; a cell body disposed on the chromium alloy vessel; Equipped with the first alloy member has a plurality of communicating holes that communicate with the internal space, the cell main body is disposed on the first alloy member so as to cover the plurality of communication holes; Metal-supported electrochemical cells.
Citation Information
Patent Citations
Joining material of solid electrolyte fuel cell stack and its joining method
JP1996130022A
Inorganic adhesive, semiconductor device using the same and its production
JP1997217039A
Solid electrolyte fuel cell
JP1998106596A
Sealing material for low-temperature operation solid oxide fuel cell
JP2004039573A
Metal support solid oxide fuel cell and manufacturing method therefor
JP2016207630A